The Elite - Book 2 - Cass, Kiera (New York : HarperTeen, 2013)
"Sixteen-year-old America Singer is one of only six girls still competing in the Selection--but before she can fight to win Prince Maxon and the Illean crown, she must decide where her own heart truly lies"--
Keywords: Marriage -- Juvenile fiction; Contests -- Juvenile fiction; Social classes -- Juvenile fiction; Princes -- Juvenile fiction; Man-woman relationships -- Juvenile fiction; Revolutionaries -- Juvenile fiction; Marriage -- Fiction; Contests -- Fiction; Social classes -- Fiction; Princes -- Fiction; Love -- Fiction; Revolutionaries -- Fiction